INNOVATIVE METHODS OF TEACHING BIOLOGY - Xudoyberdiyeva Roziya Melikulovna (The Conference Hub, 2025)
Traditional methods of teaching biology, often reliant on rote memorization and didactic lectures, frequently fail to engage students fully or foster critical thinking skills essential for the 21st century. This article explores a range of innovative pedagogical approaches designed to transform biology education from a passive information transfer model to an active, inquiry-driven, and student-centered learning experience. We delve into the integration of active learning strategies such as problem-based learning, case studies, and collaborative projects, alongside advanced technological tools including virtual laboratories, augmented reality, and gamification. Furthermore, the importance of experiential learning through field trips, authentic laboratory work, and citizen science initiatives is highlighted. By adopting these innovative methods, educators can enhance student engagement, deepen conceptual understanding, cultivate scientific literacy, and prepare students for complex real-world challenges in biology and beyond.
Keywords: Innovative teaching, biology education, active learning, technology integration, problem-based learning, gamification, scientific literacy, experiential learning.